2019
DOI: 10.1590/0103-8478cr20180917
|View full text |Cite
|
Sign up to set email alerts
|

Physicochemical and microbiological stability of mixed nectar of orange and uvaia

Abstract: The addition of Cerrado fruits to juice and nectar formulations is an interesting alternative for the beverage industry, as it allows developing innovative products containing nutritive and bioactive compounds. Thus, the objective of this study was to produce mixed nectar of orange and uvaia, using orange nectar as a control, and to evaluate physicochemical and microbiological characteristics of beverages during the storage. Mixed nectar formulations were prepared with the addition of uvaia pulp and orange jui… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 19 publications
0
4
0
1
Order By: Relevance
“…De acordo com os estudos de López et al (2019) que analisou uma mistura de néctar elaborado de cenoura, laranja e beterraba, o teor de açúcares redutores aumentou durante o tempo de armazenamento em todos os néctares, em um meio com baixo pH como o do suco e do néctar de goiaba avaliados, os ácidos podem se transformar em açúcares redutores, o que justifica os valores obtidos. Tomaz et al (2019) que analisou a estabilidade do néctar misto de laranja e uvaia, percebeu que o processo de pasteurização contribuiu para a hidrólise do açúcar, sendo responsável pelos níveis mais elevados de açúcar redutor presente na bebida.…”
Section: Resultsunclassified
“…De acordo com os estudos de López et al (2019) que analisou uma mistura de néctar elaborado de cenoura, laranja e beterraba, o teor de açúcares redutores aumentou durante o tempo de armazenamento em todos os néctares, em um meio com baixo pH como o do suco e do néctar de goiaba avaliados, os ácidos podem se transformar em açúcares redutores, o que justifica os valores obtidos. Tomaz et al (2019) que analisou a estabilidade do néctar misto de laranja e uvaia, percebeu que o processo de pasteurização contribuiu para a hidrólise do açúcar, sendo responsável pelos níveis mais elevados de açúcar redutor presente na bebida.…”
Section: Resultsunclassified
“…Similarly, Tomaz et al . (2019) found that incorporating 20–30% uvaia pulp into orange nectar significantly increased levels of ascorbic acid and phenolic compounds, with a notable improvement in microbiological stability observed with a 30% pulp addition. Justino et al .…”
Section: Conservation and Processing Methods Of Uvaia: Opportunities ...mentioning
confidence: 99%
“…Tomaz et al . (2019) found that the ascorbic acid content in uvaia pulp surpasses orange juice by 40%, underscoring uvaia's potential as an alternative vitamin C source. Consuming 100 g of uvaia fruit can exceed the recommended daily intake of vitamin C for adults (75 mg for women and 90 mg for men) (Institute of Medicine, 2000).…”
Section: Compositionmentioning
confidence: 99%
“…In this context, uvaia fruits (Eugenia pyriformis Cambess) could stand out, and this species is characterized by yellow-orange color, as well as presenting adequate properties for the production of beverages, ice cream, and jams (Reitz et al, 1988;Silva et al, 2008;Gomes, 2012;Tomaz et al, 2019). Uvaia has high phenolic compounds and ascorbic acid contents when compared to other Brazilian fruits (Rufino et al, 2010;Silva et al, 2014;Zillo et al, 2014), which improves its antioxidant potential, contributing to the reduction of oxidative stress and the risk of developing cardiovascular diseases (Lopes et al, 2018).…”
Section: Fabricação De Néctar De Uvaia E Avaliação Da Estabilidade Fí...mentioning
confidence: 99%
“…The acidic character of uvaia can be a relevant factor for the preservation of the beverage, once it allows reducing the development of undesirable microorganisms and increases the oxidative stability of ascorbic acid during the storage. The acidulating potential of organic acids combined with pH reduction is an important mechanism for reducing microbial growth and ascorbic acid degradation (Bedetti et al, 2013;Massager, 2005;Maeda et al, 2006;Tomaz et al, 2019) The results in Table 4 show that, concerning the freshly prepared beverage, the ascorbic acid concentration was higher for the formulation F3, due to the higher uvaia pulp concentration. Similar ascorbic acid concentrations were observed for the formulations with the addition of 40% and 50% of pulp after 30 and 90 days of storage, indicating that these formulations can provide the same content of this vitamin during the periods studied.…”
Section: Parametersmentioning
confidence: 99%